Upaya Pengembangan Kognitif Anak Melalui Kegiatan Bermain Mengenal Warna Usia 4-5 Tahun - Fitri Yanti; Musnar Indra; Rizki Amalia (Jurnal Pendidikan Tuntas, 2023)
The low cognitive development of children aged 4-5 years in Kejora Bangsa Kindergarten were the reason why this research was done. One of the activities offered by researchers to solve this problem is the activity of playing to know colors. The research used was classroom action research with 2 cycles and 2 meetings in each cycle, while the data collection technique used was observation and documentation techniques. The results of the research that was a significant cognitive increase in children as follows: the BB value at pre-action with a total of 10 children the percentage was 64.28%, in the first cycle the percentage was 3 children to 17.81%, in the second cycle there were 0 children the percentage was 0% As for the MB value in the pre-action with 1 child the percentage was 7.14%, in the first cycle it became 4 children the percentage was 28.57%, in the second cycle it became 0 children the percentage was 0%. As for the BSH value in pre-action with 4 children the percentage was 28.57%, in cycle I it became 1 child the percentage was 7.14%, in cycle II it became 2 children the percentage was 11.76%. As for the BSB value in Pre-action with 0 children the percentage was 0%, in the first cycle there were 7 children the percentage was 47.60%, in the second cycle there were 13 children the percentage was 88.23%. Based on the results of the research above, it is recommended that teachers be able to use color recognition play activities as an alternative way to improve children's cognitive abilities. Keywords: Cognitive, Recognizing colors, Classroom Action Research